Implementation of the Multiple Intelligences Method at Bahtera Multiple Intelligence Preschool Malaysia - Nurrachmah, Farah Khalda; Agustin, Mubiar; Muqodas, Idat; Mustafa, Lily Muliana (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to explore the implementation of a Multiple Intelligences-based curriculum in Bahtera Multiple Intelligence Preschool Malaysia, applied to children aged three to four years with a total of 12 participants. Research on Multiple Intelligences is important considering that education today still places greater emphasis on linguistic and logical-mathematical intelligence, while other types of intelligence are not yet optimally facilitated. This has negative impacts on children’s personality development, such as feelings of shyness, fear, and low self-esteem. Methods: This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation of the process of implementing the Multiple Intelligences method for children aged three to four years. Data analysis used Miles and Huberman’s model, assisted by NVivo 12 Plus software to support systematic coding, organization, and visualization of thematic relationships among learning strategies, challenges, and solutions in the implementation of the Multiple Intelligences method. Results: The findings indicate that children’s intelligence is not only measured by IQ but also by various other intelligences according to their individual characteristics. Play-based activities proved effective in fostering children’s multiple intelligences. The initial identification of each child’s dominant intelligence, supported by questionnaires and teacher observations, was a key factor in applying Multiple Intelligences-based methods tailored to the needs of each child. Thus, the stimuli provided by teachers were aligned with the developmental stages of children’s intelligences. Novelty: The novelty of this research lies in its comprehensive examination of all aspects of multiple intelligences integrated into a specialized curriculum, beginning with observation to identify each child’s dominant intelligence.